2005
DOI: 10.1111/j.1443-1661.2005.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Autofluorescence Imaging Videoscope System for the Detection of Colonic Neoplasms

Abstract: Background: Previously, we reported that most gastrointestinal tumors could be distinguished with the Light-Induced Fluorescence Endoscopy for GastroIntestine system (LIFE-GI system) using a fiberscope. However, the quality of the fiberscopic images was inferior compared with videoscopic images. Therefore, we developed a new Auto-Fluorescence Imaging (AFI) videoscope system (manufactured by Olympus Corp.). Methods: We evaluated the clinical usefulness of the AFI videoscope system for the detection of colonic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…A non-invasive method of diagnosis could remove the need for physical biopsy and provide improvements in diagnostic accuracy for a number of diseases. Although several novel imaging techniques that can be operated in conjunction with standard WLE have recently become available in the clinical setting -such as narrow-band imaging (NBI) [8], autofluorescence imaging (AFI) [9] and more recently confocal endomicroscopy (CLE) [10,11] -there is still no red flag technique for detection of GI premalignant lesions that can progress into cancer. Furthermore, there is currently no technology that can reliably indicate when it is appropriate not to biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…A non-invasive method of diagnosis could remove the need for physical biopsy and provide improvements in diagnostic accuracy for a number of diseases. Although several novel imaging techniques that can be operated in conjunction with standard WLE have recently become available in the clinical setting -such as narrow-band imaging (NBI) [8], autofluorescence imaging (AFI) [9] and more recently confocal endomicroscopy (CLE) [10,11] -there is still no red flag technique for detection of GI premalignant lesions that can progress into cancer. Furthermore, there is currently no technology that can reliably indicate when it is appropriate not to biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of using AFI for detecting cancers in the digestive tract including the esophagus, stomach, and colon has been reported as has the effectiveness of the AFI system for the detection of colorectal neoplasias [9, 11]. In addition, McCallum et al reported that AFI colonoscopy may be a valuable tool for the virtual distinction between adenomatous and hyperplastic polyps [12].…”
Section: Discussionmentioning
confidence: 99%
“…During AFI observation, non-neoplastic lesions appear green, whereas neoplastic lesions have a magenta (reddish purple) image. 34,35 The usefulness of AFI for differential diagnosis between neoplastic and nonneoplastic lesions has been reported; [36][37][38][39][40][41] however, studies evaluating AFI for colon polyp detection have generated conflicting results.…”
Section: Autofluorescence Imagingmentioning
confidence: 99%